Food capture and escape behavior of Leposternon microcephalum Wagler, 1824 (Squamata: Amphisbaenia) - Reiche,H. (2024)
Abstract Amphisbaenians are fossorial reptiles that have a cylindrical and elongated body covered with scales arranged in rings, and are all apodal, except for the three species of the genus Bipes. The amphisbaenian diet consists of a variety of invertebrates and small vertebrates. As these animals live underground, many aspects of their natural history are difficult to study. Most feeding studies of amphisbaenians have focused on the composition of the diet and feeding ecology, and the data available on feeding behavior are based on precursory observations. The present study describes the food capture behavior of Leposternon microcephalum Wagler, 1824 in captivity. In this experiment we used non-live bait (moist cat food), which was placed near a burrow opening, on the surface of the substrate. Three animals were monitored visually and filmed using cellphone cameras deployed at fixed points, to capture images from the dorsal and lateral perspectives of the study subjects. Two principal types of behavior were observed: the capture of food and defense mechanisms. The strategies used to capture the food were similar to those observed in other fossorial species. Although the backward movement has already been observed and described, we were able to record this movement being used as an escape strategy. These findings enrich our knowledge on different aspects of the natural history of the amphisbaenians.